Why Won't Aliens Talk to Us? Content and Community Dynamics in Online Citizen Science - Luczak-Roesch, Markus; Tinati, Ramine; Simperl, Elena; van Kleek, Max; Shadbolt, Nigel; Simpson, Robert (Proceedings of the International AAAI Conference on Web and Social Media, 2014)
We conducted a quantitative analysis of ten citizen science projects hosted on the Zooniverse platform, using a data set of over 50 million activity records and more than 250,000 users, collected between December 2010 and July 2013. We examined the level of participation of users in Zooniverse discussion forums in relation to their contributions toward the completion of scientific (micro-)tasks. As Zooniverse is home to a multitude of projects, we were also interested in the emergence of cross-projects effects, and identified those project characteristics, most importantly the subject domain and the duration of a project. We also looked into the adoption of expert terminology, showing that this phenomenon is dependent on the scientific domain which a project addresses but also affected by how the communication features are actually used by a community. This is the first study of this kind in this increasingly important class of online community, and its insights will inform the design and further development of the Zooniverse platform, and of citizen science systems as a whole.